The use of quality function deployment to help adopt a total quality strategy - Smith, J. A.; Angeli, Ioannis (My University, 1995)
This paper compares the requirements of the International Quality Assurance Management System Standard ISO 9000 with the philosophies offive of the leading quality gurus: Crosby, Deming, Feigenbaum, Ishikawa and Juran. A quality function deployment (QFD) matrix is used for this purpose. The 20 requirements of ISO 9000 are idented as the 'what' on the vertical axis, and the main points of thefive gurus as the horizontal 'hows'. The relationships are studied in the body of the matrix. The roof of the 'house of quality' is used to analyze the correlation between the philosophies of the gurus. Consideration is then given as to how the model presented can be customized to allow companies to use this approach to help develop a total quality strategy. © 1995, Taylor & Francis Group, LLC. All rights reserved.
Keywords: International Quality Assurance Management System Standard; Quality function deployment